Overactivation of calcineurin induced by amyloid-beta and prion proteins - Agostinho, Paula (2008)
Amyloid-beta protein (A[beta]) and the scrapie isoform of prion protein (PrPSs) have a central role in the pathogenesis of Alzheimer's disease (AD) and prion-related encephalopathies (PRE), respectively. In both disorders, the deposition of these misfolded proteins is accompanied by apoptotic neuronal loss. However, the pathogenesis and molecular basis of A[beta]- and PrPSc-neurotoxic effects are not completely understood. The Ca2+/calmodulin-dependent phosphatase calcineurin (CaN), through the dephosphorylation of the proapoptotic protein BAD, may be the link between Ca2+homeostasis deregulation and apoptotic neuronal death. In this study we used primary cultures of rat brain cortical neurons in order to investigate whether A[beta] and PrP affect CaN activity. We observed that synthetic peptides of A[beta] (A[beta]25-35 and A[beta]1-40) and PrP (PrP106-126) increased CaN activity, but did not affect the levels of this protein phosphatase. Moreover, we found that these peptides reduced the levels of BAD phosphorylated at serine residue 112, and this effect was prevented by the CaN inhibitor FK506. Since dephosphorylated BAD translocates to mitochondria, where it triggers cytochrome c release, we determined the levels of BAD in mitochondrial and cytosolic fractions. The data obtained showed that A[beta]- and PrP-treated neurons had higher levels of BAD in mitochondria than control neurons. This increase in mitochondrial BAD levels was matched by a decrease in cytochrome c. FK506 prevented the alterations of mitochondrial BAD and cytochrome c levels induced by A[beta] and PrP peptides. Taken together the data suggest that A[beta] and PrP increased CaN activity, inducing BAD dephosphorylation and translocation to mitochondria and, subsequently, cytochrome c release that may trigger an apoptotic cascade. Therefore, therapeutic strategies targeting CaN might be valuable for these neurodegenerative disorders.